The Effect of Giving Additional Feed Sente (Homalomena cordata scoot) on The Performance of Duroc Farming Pig - P., Yusadana; Budaarsa, K.; Mahardika, I G. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of adding sente (Homalomena Cordata Scoot) in the ration on the performance of pigs. The study was carried out for 3 months in the race of pig farms in Delodceking Banjar, Lumbung Kauh Village, Selemadeg Barat District, Tabanan Regency. The design used was a randomized block design (RBD) consisting of 4 treatments 4 grup as a test. Four treatments were given, namely commercial ration (concentrate + rice bran) without sente (A) as control, commercial ration (concentrate + sente) 2% plus sente (B), commercial ration (concentrate + sente) 4% plus cente (C), 6% commercial ration (concentrate + rice bran) plus cente (D). The variables observed included initial body weight, final body weight, weight gain, feed consumption, FCR and the price of ration per 1 kg of the United Nations. The data obtained were analyzed by analysis of variance, if there were significantly different results (P <0.05) then followed by Duncans multiple distance test. The results showed that the addition of a commercial ration with a cente to a level of 6% gave a not significant effect on the performance of race pigs, but was able to decrease the cost of rations. Pigs which are maintained by giving commercial rations with the addition of 6% cente have a lower economic value compared to the control ration. Keywords: Commercial Ration, S ente (Homalomena Cordata Scoot) , Duroc Farming Pig